2020
DOI: 10.3390/microorganisms8070980
|View full text |Cite
|
Sign up to set email alerts
|

Fungistatic Action of N-Acetylcysteine on Candida albicans Biofilms and Its Interaction with Antifungal Agents

Abstract: Therapies targeted to fungal biofilms, mainly against the matrix, and therapies that do not induce microbial resistance are relevant. N-acetylcysteine (NAC), a mucolytic agent, has shown antimicrobial action. This study evaluated the effect of NAC against fluconazole-susceptible (CaS) and -resistant (CaR) Candida albicans. The susceptibility of planktonic cultures to NAC, the effect of NAC on biofilms and their matrix, the interaction of NAC with antifungal agents, and confocal microscopy were evaluated. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
(101 reference statements)
2
7
0
Order By: Relevance
“…It has been suggested that abundant cell wall proteins are interconnected by disulfide bridges, e.g., protein Pga59 and Pga62 which are GPI cell wall protein with cysteine residues, in addition, Pga59 and Pga62 are expressed to much higher levels in biofilms than in planktonic cultures [59] and they are required for cell wall integrity [58] . The above is consistent with the observations about effect of N-acethylcysteine on C. albicans biofilms [68] , [69] . In general, anti-biofilm activity of N-acethylcysteine is based on the breaking of disulfide [68] , [69] .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that abundant cell wall proteins are interconnected by disulfide bridges, e.g., protein Pga59 and Pga62 which are GPI cell wall protein with cysteine residues, in addition, Pga59 and Pga62 are expressed to much higher levels in biofilms than in planktonic cultures [59] and they are required for cell wall integrity [58] . The above is consistent with the observations about effect of N-acethylcysteine on C. albicans biofilms [68] , [69] . In general, anti-biofilm activity of N-acethylcysteine is based on the breaking of disulfide [68] , [69] .…”
Section: Resultssupporting
confidence: 92%
“…The above is consistent with the observations about effect of N-acethylcysteine on C. albicans biofilms [68] , [69] . In general, anti-biofilm activity of N-acethylcysteine is based on the breaking of disulfide [68] , [69] . But in term of amino acid composition, it has been determined that the content of thiolated amino acids, i.e., cysteine and tyrosine, forming the wall cell are 2.7 and 3.4%, respectively [60] .…”
Section: Resultssupporting
confidence: 92%
“…These problems are a challenge for humanity, especially when considering that the development of new drugs demands time and money. Thus, the repurposing of existing medications and alternative therapies, such as natural substances, has been investigated [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate those of previous studies that showed that DNase reduced WSP levels (Flemming et al, 2007; Martins et al, 2012; Panariello et al, 2019). The manana‐glucan complex (MGCx), present in the ECM of C. albicans biofilms, is formed via the interaction of WSPs (α‐mannans) and ASPs (β‐glucans) (Nunes et al, 2020; Panariello et al, 2017). The stability of these polysaccharides is responsible for maintaining the integrity of the MGCx, and the interactions in this complex are responsible for the antifungal resistance of biofilms (Perezous et al, 2005).…”
Section: Discussionmentioning
confidence: 99%